Psychological Assessment: Identification, Detection of Potential and Problems of Children with Special Needs at UPTD LDPI, Padang City - Rozi Sastra Purna; Fitri Angraini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
So far, the learning strategy implemented in schools is still widespread, providing all students with the same educational treatment and services. These students have different levels of skills, intelligence, interests, and talents. Therefore, early identification is needed to detect children's learning potential and problems. The results of the identification can later be used by teachers in implementing learning processes that suit the characteristics of students. The method used in identification is an intelligence test using the Stanford-Binet Intelligence Scale and Culture Fair Intelligence Scale instruments. In contrast, the method used in conveying examination results is lectures and discussions with parents and teachers regarding the characteristics of children with special needs and appropriate services and education. The identification results found that one student (1.56%) was in the immobile category, seven students (10.94%) were in the debilitated category, 13 students (20.31%) were in the borderline category, 15 students (23.44%) were in the low average category, 22 students (34.38%) were in the average category, and six students (9.38%) were in the high average category. This activity had been carried out well. Through discussions and counseling, parents and teachers gained an understanding of treatment and educational services that suit the characteristics of each child. In the future, follow-up activities will likely be related to evaluating learning strategies and student abilities.